2005
DOI: 10.1007/bf03074206
|View full text |Cite
|
Sign up to set email alerts
|

Werk, uitval en reïntegratie bij patiënten met ME/CVS

Abstract: Samenvatting Doel van dit onderzoek was inzicht te krijgen in het werk, de beperkingen, gepercipieerde oorzaken, behandelingen en veranderingen na werkhervatting van ME/CVS-patie¨nten in Nederland. Een vragenlijstonderzoek is uitgevoerd bij 1035 ME/CVSpatie¨nten, via drie uitvoeringsinstellingen, de MEpatie¨ntenvereniging en belangenvereniging.Van de ME/CVS-patie¨nten werkte 30% op het moment van invullen van de vragenlijst. Veel patie¨nten rapporteerden ernstig beperkt te zijn in het uitvoeren van forse inspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 3 publications
1
7
0
Order By: Relevance
“…The percentage able to work 24 to 40 h decreased from 43% to 4% and the percentage of patients who were able to work 0 to 8 h increased from 1.4% to 28%. These are similar to the findings by TNO (The Netherlands Organisation for Applied Scientific Research) [2], a renowned independent Dutch research institute.…”
Section: Employment Status In Me/cfssupporting
confidence: 88%
See 4 more Smart Citations
“…The percentage able to work 24 to 40 h decreased from 43% to 4% and the percentage of patients who were able to work 0 to 8 h increased from 1.4% to 28%. These are similar to the findings by TNO (The Netherlands Organisation for Applied Scientific Research) [2], a renowned independent Dutch research institute.…”
Section: Employment Status In Me/cfssupporting
confidence: 88%
“…Collin et al [46] who analysed the NHS database (n = 2170) found that 41% were employed and 50% had discontinued work due to ME/CFS which is similar to the 54% found by a systematic review by Ross et al [59]. TNO, an independent Dutch research institute [2] (n = 924) found that 30% were working; 7% had never been on long-term sick leave and 23% had been able to go back to work after long-term sick leave but they were working less hours. They were also less often involved in management and more often did sedentary work behind a computer.…”
Section: Employment Statusmentioning
confidence: 53%
See 3 more Smart Citations